Association Between Tracheostomy and Functional, Neuropsychological, and Healthcare Utilization Outcomes in the RECOVER Cohort - Sangeeta Mehta, MD; Anita Brondani, MD; George Tomlinson, PhD; Leslie Chu, BSc; Stacey Burns, RN; Andrea Matte, BSc; Jill I. Cameron, PhD; Jan O. Friedrich, MD; Jill Rudkowski, MD; Priscila Robles, PhD; Yoanna Skrobik, MD; Margaret Herridge, MD; et al. (Critical Care Explorations, 2022)
OBJECTIVES:. Tracheostomy is commonly performed in critically ill patients requiring prolonged mechanical ventilation (MV). We evaluated the outcomes of tracheostomy in patients who received greater than or equal to 1 week MV and were followed for 1 year. DESIGN:. In this secondary analysis of a prospective observational study, we compared outcomes in tracheostomy versus nontracheostomy patients. Outcomes post ICU included Functional Independence Measure (FIM) subscales, 6-Minute Walk Test (6MWT), Short Form 36 (SF36), Medical Research Council (MRC) Scale, pulmonary function tests (PFTs), Impact of Event Scale (IES), Beck Depression Inventory-II (BDI-II), and vital status and disposition. SETTING:. Nine University affiliated ICUs in Canada. PATIENTS:. Medical/surgical patients requiring MV for 7 or more days who were enrolled in the Towards RECOVER Study. MEASUREMENTS AND MAIN RESULTS:. Of 398 ICU survivors, 193 (48.5%) received tracheostomy, on median ICU day 14 (interquartile range [IQR], 8–0 d). Patients with tracheostomy were older, had similar severity of illness, had longer MV duration and ICU and hospital stays, and had higher risk of ICU readmission (odds ratio [OR], 1.9; 95% CI, 1.0–3.2) and hospital mortality (OR, 2.6; 95% CI, 1.1–6.1), but not 1-year mortality (hazard ratio, 1.41; 95% CI, 0.88–1.2). Over 1 year, tracheostomy patients had lower FIM-Total (7.7 points; 95% CI, 2.2–13.2); SF36, IES, and BDI-II were similar. From 3 months, tracheostomy patients had 12% lower 6MWT (p = 0.0008) and lower MRC score (3.4 points; p = 0.006). Most PFTs were 5–8% lower in the tracheostomy group. Tracheostomy patients had similar specialist visits (rate ratio, 0.63; 95% CI, 0.28–2.4) and hospital readmissions (OR, 0.82; 95% CI, 0.54–1.3) but were less likely to be at home at hospital discharge and 1 year. CONCLUSIONS:. Patients who received tracheostomy had more ICU and hospital care and higher hospital mortality compared with patients who did not receive a tracheostomy. In 1 year follow-up, tracheostomy patients required a higher daily burden of care, expressed by FIM.